(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the relationship between language and consciousness in the psychological interpretation of L.S.Vygotsky. Vygotsky’s theory of the influence of language on the formation of consciousness is analyzed, the key aspects of this interaction are considered and our own conclusions are offered.